Contextualized music listening: playlists and the Mehrabian and Russell model - Krause, Amanda; North, Adrian (Springer, 2014)
The present research considered everyday music listening in the context of eight situations, classified as high or low on Mehrabian and Russell’s (1974) Pleasure-Arousal-Dominance (PAD) dimensions. Completing a questionnaire, 344 participants considered the music they would select and created a playlist for a given situation. The music selected by participants (as playlists) for these eight situations differed along two dimensions, namely arousing and aesthetic. Rather than selecting music that would moderate arousal (Berlyne, 1971), results indicated that participants employed an arousal-optimization strategy. There were also differences in the music selected across situations on the aesthetic dimension. The findings also suggest that music chosen for situations is subject to injunctive norms, such that there was considerable variation between the music chosen for listening to on public transport or when washing dishes, whereas music selected for a wedding was perceived as more homogeneous. While previous research has considered music preference in terms of pleasure and arousal, the apparent role of injunctive norms may be related to dominance and requires additional research. More generally, the results indicate that Mehrabian and Russell’s PAD dimensions offer a useful framework for considering the relationship between music and the environmental context in which it is experienced.